Effect of thermal annealing on gas separation performance and aggregation structures of block polyimide membranes. (26th March 2021) - Feng, Yuxuan; Ren, Jizhong; Li, Hui; Zhao, Dan; Sheng, Lujie; Wu, Yongdong; Zhao, Wenyuan; Deng, Maicun
Abstract: Block polymers with thermal annealing are attractive routes to produce 6FDA-based polyimide membranes with enhanced gas separation performance. However, some 6FDA-based polyimide membranes exhibit different gas separation behavior trends under the thermal annealing process. In this work, two 6FDA-DETDA/DMMDA block polyimide membranes with different 6FDA-DETDA block lengths were prepared and annealed at three temperatures (150 °C, 250 °C and 350 °C). To investigate the thermal annealing process and its influence on the thermal cross-linking behavior and aggregation structures, in situ XRD and ambient-pressure X-ray photoelectron spectroscopy (AP-XPS) were employed. Based on the orbital-weighted Fukui function calculated by Time-dependent density functional theory (TD-DFT) and AP-XPS spectra, it's found that free radicals cross-linking that induced by 350 °C annealing occurred in imide rings, and resulted in the destroyed imide rings and decreased average interchain distances in both block polyimides. However, the massive 6FDA-DETDA block hindered imide rings from destruction and resulted in a slight molecular filtration, which benefited the gas transport of small kinetic diameter gases. As a result, 350 °C annealed membrane of bPI-2 exhibited enhanced gas separation performance. We expect that this work will shed light on the effect of thermal annealing on the gas separation behavior of block polyimides and offer a way to tune gas separation performance by thermal annealing. Graphical abstract: Image 1 Highlights: 6FDA-DETDA/DMMDA block polyimides with different block lengths were synthesized. In situ XRD and AP-XPS were used to observed changes in d-spacing and N1s spectra. Both 250 °C annealed membranes had remarkable increases in all gas permeabilities. Imide rings opened and induced cross-linking during 350 °C annealing. Massive 6FDA-DETDA block limited chain motion and cross-linking.